Rare and challenging two complications after prostate biopsy of an older man - Turgut, Tuğba; Mut Sürmeli, Deniz; Bahşi, Remzi; Selvi Öztorun, Hande; Varlı, Murat (Journal of Surgery and Medicine, 2018)
Although prostate cancer is the second most common cancer type in men, its mortality rate is lower. Despite European Randomized Study of Screening for Prostate Cancer study reported that screening with prostate-specific antigen made a substantial reduction in prostate cancer mortality at 13 years of follow-up; they do not recommend population screening with prostate specific antigen because of the uncertain balance between benefits and harms. In our case, prostate biopsy was performed because of urinary symptoms but two severe operation planned due to infective endocarditis and spondylitis, a long and serious antibiotherapy process and its side effects were occurred after prostate biopsy. In light of this case, clinicians should consider that prostate biopsy may cause serious complications when they are screening asymptomatic men for prostate cancer or deciding whether or not to have a prostate biopsy.